Being a Moral Student: Content Analysis of Anti-Corruption Education Textbooks in Indonesia - Yanto, Murni; Masuwd, Mowafg; Wanto, Deri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to analyze the content of existing anti-corruption education textbooks in Indonesian universities. The significance of this research lies in revealing the limitations of these textbooks, which only cover basic aspects and do not sufficiently stimulate students' emotions and enthusiasm regarding the dangers of corruption. To address this issue, the study employs a content analysis approach to examine several anti-corruption education textbooks in Indonesia. The commonly used steps in data analysis include traditional content analysis, which involves a preparatory stage, an organizing stage, and the reporting of results. Procedures typically used in this method include text categorization and cross-tabulation of emerging categories. The study successfully identified that the direction and format of the content in these textbooks are still limited to aspects such as